Germany's Drive to the West (Drang Nach Westen) A Study of Germany's Western War Aims during the First World War - Gatzke, Hans W. (Johns Hopkins University Press, 2019)
Originally published in 1950. Hans Gatzke analyzes Germany's ambitions to expand westward during World War I. Germany's wartime plans for expansion to the west had important repercussions at home and abroad. Gatzke proceeds chronologically, starting with the German political parties' outlining of their war aims. Gatzke claims that a combination of interests, including those of industrialists, pan-Germans, the parties of the Right, and the Supreme Command was responsible for the stubborn propagation of Germany's large war aims, which condemned the German people to remain at war until the bitter end. Each of these forces had its own particular reasons for wanting to hold out for far-reaching territorial gains, yet one aim that most of them had in common was ensuring, through a successful peace settlement, the continuation of the existing order, to their own advantage and to the political and economic detriment of the majority of the German people.